Pharmaceutical Care: new perspectives on pharmaceutical performance in the face of the COVID-19 pandemic (Research, Society and Development, 2022)
The pandemic caused by the SARS-CoV-2 virus has directly affected all areas of society. Especially in the area of ​​health, it had – and still has – enormous importance in dealing with the effects brought by it, so the role of pharmacists was also essential to face this disease. This study aims to analyze how the pharmaceutical professional contributed, from the perspective of pharmaceutical care, to the recovery of patients affected by the coronavirus and to the prevention of infection by the virus, through the methodology of qualitative literature review, in order to reflect and confront similar themes evidenced in the specialized literature. It was noticed, through the research, that the pandemic caused the entire configuration of patient care to be rethought, aiming to meet the most urgent demands as a result of this disease, so the pharmacist contributed immeasurably to the prevention and treatment of patients. individuals who were affected by the disease, through action strategies for the management of medicines and pharmacies, reduction of self-medication and the search for the rational use of medicines, in addition to helping society in general, by clarifying any doubts, fighting false ones. disseminated information, as well as multidisciplinary action together with other health professionals.